Two-part curable composition
By using a combination of methacrylate and amine compositions with fatty acid peroxide in the binder, the problem of insufficient opening time and curing characteristics in the prior art is solved, and long opening time and rapid opening time at room temperature are achieved Curing effect.
Patent Information
- Application Number
- CN202080093726.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-17
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-12-17
AI Technical Summary
Existing methacrylate based adhesive compositions lack sufficient opening time and sharpening curing characteristics in assembly applications to meet most assembly needs.
Using a two-part curable composition, part of which contains the methacrylate component and amine and the other part contains fatty acid peroxide, exhibits an opening time of at least 3 hours when mixed at room temperature and reaches a peak within less than 1 hour Curing temperature, the curing process is controlled by adjusting the component ratio and additives.
Long opening time and sharpening curing characteristics of the composition at room temperature ensure the stability and rapid curing properties of the adhesive in application.
Smart Images

Figure CN114981332B_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a two-part curable composition comprising a first part containing a (meth)acrylate component and an amine and a second part containing a fatty acid peroxide. Background Art
[0002] Acrylic acid-based adhesive compositions are well known. See, for example, U.S. Pat. No. 4,536,546 (Briggs). Adhesives based on this technology appear to have been sold by Illinois ToolWorks Inc. of Chicago, Illinois, under the trade names PLEXUS MA 300 and 310. These adhesives can exhibit an unpleasant odor, and their handling is toxic, which can be considered a significant disadvantage for their use.
[0003] U.S. Patent Application Publication No. 2010 / 0065210 provides an anti-sagging composition comprising: (a) a first part comprising: (i) a (meth) acrylic component, (ii) an amine catalyst; (iii) an optional second catalyst; (iv) a reactive acid component, and (v) a free radical inhibitor; and (b) a second part comprising: (i) a resin component containing epoxy groups, (ii) a peroxide; and (iii) a metal compound, the metal compound complexed with a strong acid component and substantially unreactive with the peroxide. The first part and the second part have sufficiently low viscosities to be easily dispensed with a pumping device. To form the adhesive, the first part is mixed with the second part, and immediately after mixing, the mixture has a higher viscosity so that after application to a surface, the adhesive does not sag, drip or migrate within the open time of the mixture, and then the mixed first and second parts are cured. The term "open time" refers to the time elapsed between mixing and curing of the adhesive.
[0004] U.S. Patent No. 9,574,118 (Cheng) relates to an adhesive composition comprising:
[0005] (a) Part I, which contains:
[0006] (i) a (meth)acrylic component, at least a portion of which comprises isobornyl (meth)acrylate;
[0007] (ii) an amine catalyst;
[0008] (iii) vinyl terminated polybutadiene in liquid form at room temperature;
[0009] (iv) a reactive acid component;
[0010] (v) solid zinc (meth)acrylate;
[0011] (vi) zinc and / or bismuth complexes; and
[0012] (vii) free radical inhibitors;
[0013] and
[0014] (b) Part II, which contains:
[0015] (i) a resin component containing an epoxy group;
[0016] (ii) benzoyl peroxide;
[0017] (iii) plasticizers; and
[0018] (iv) optionally a block copolymer,
[0019] Therein, the first part and the second part are mixed and applied to at least one substrate.
[0020] U.S. Patent No. 8,921,490 (Levandoski) relates to a two-part curable halogen-free composition comprising:
[0021] a. The first part, which contains:
[0022] i. at least one (meth)acrylate monomer;
[0023] ii. a first halogen-free elastomer, wherein the first halogen-free elastomer comprises a styrene-butadiene-styrene block copolymer;
[0024] iii. Acid catalyst;
[0025] iv. a free radical initiator; and
[0026] v. Free radical stabilizers; and
[0027] b. The second part, which contains:
[0028] i. at least one (meth)acrylate monomer;
[0029] ii. a second halogen-free elastomer;
[0030] iii. a catalyst; and
[0031] iv. a stabilizer for stabilizing the catalyst;
[0032] The first part and the second part are combined together to form a curable composition.
[0033] U.S. Pat. No. 6,433,091 (Cheng) relates to a two-part reactive adhesive composition containing (meth)acrylates, comprising a vinyl terminated liquid rubber and a polymeric elastomer. The vinyl terminated liquid rubber is preferably a (meth)acrylate terminated polybutadiene; the polymeric elastomer is preferably a polychloroprene, a core-shell polymer and / or a block copolymer rubber.
[0034] U.S. Pat. No. 6,291,593 (Cheng) is directed to an adhesive composition consisting essentially of 10-90 wt. % ester monomers, about 2-85 wt. % polymerized elastomer, about 0.02-10 wt. % initiator, and about 0.005-7 wt. % of a retarding additive, the retarding additive being selected from aprotic Lewis acids, and zinc salts thereof, and mixtures thereof, the ester monomers being selected from methacrylate monomers, acrylate monomers, and mixtures thereof, the retarding additive being present in an amount effective to (a) extend the open time of the adhesive composition by at least 5 minutes, or (b) reduce the peak exotherm temperature of the adhesive composition by at least 15°F.
[0035] U.S. Patent No. 9,657,203 (Murray) relates to a two-part curable composition, wherein the composition comprises:
[0036] (a) Part I, which contains:
[0037] (i) (meth)acrylate component;
[0038] (ii) 1,4-quinones, such as naphthoquinone or benzoquinone and their derivatives, in an amount less than or equal to about 0.05% by weight;
[0039] (iii) a triarylphenylphosphine or an alkarylphenylphosphine in an amount greater than or equal to about 0.5 weight percent; and
[0040] (iv) amines;
[0041] and
[0042] (b) Part II, which contains:
[0043] (i) Benzoyl peroxide in an amount greater than about 1.0 weight percent.
[0044] The composition of the '203 patent, when used to adhesively join substrates, such as different substrates, one of which is comprised of a plastic such as PC / ABS and the other of which is comprised of a metal such as anodized aluminum, is reported to have an open time of at least about 2 minutes at room temperature and a fixture time of less than about 80 seconds at a tie line temperature of 40° C. The composition of the '203 patent is reported to have a shelf life of greater than 4 weeks at a temperature of 38° C.
[0045] International Patent Publication No. WO 2017 / 172270 (Messana) relates to a two-part curable composition comprising:
[0046] Part A: one or more compounds of the following structure I:
[0047]
[0048] Where A is CH2 or benzyl, R is C 1-10 Alkyl, R' is H or C 1-10 alkyl, or R and R' together may form a four- to seven-membered ring fused to a benzene ring, R" is optional, but when R" is present, R" is halogen, alkyl, alkenyl, cycloalkyl, hydroxyalkyl, hydroxyalkenyl, alkoxy, amino, alkylene ether or alkenylene ether, alkylene (meth)acrylate, carbonyl, carboxyl, nitroso, sulfonate, hydroxyl or haloalkyl, and EWG is an electron withdrawing group; and
[0049] Part B: Oxidizing agent,
[0050] At least one of part A or part B comprises a (meth)acrylate component.
[0051] Despite the above state of the art, existing compositions do not possess the desired combination of long open time properties and sharp cure characteristics required for many assembly applications. Thus, a need for such compositions still exists.
[0052] To date, this need remains unmet. Summary of the invention
[0053] In one aspect, a two-part curable composition is provided, wherein the composition comprises:
[0054] (a) Part A composition, the composition comprising:
[0055] (i) a (meth)acrylate component; and
[0056] (ii) amines;
[0057] and
[0058] (b) a part B composition comprising:
[0059] (i) Fatty acid peroxides.
[0060] When the Part A composition and the Part B composition are mixed together at room temperature (i.e., room temperature is about 25° C.), the mixed composition exhibits an open time of at least about 3 hours, but then reaches its peak cure temperature (or Tc) in less than about 1 hour. 峰 ), measured by a PICO Technologies USB TC-08 thermocouple data logger.
[0061] In another aspect, the present invention provides a method of improving the open time of a two-part curable composition and sharpening the time difference between the temperature at which the onset of cure begins and the peak cure temperature achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 Shown is a graph of cure temperature versus time collected by a PICO Technologies USB TC-08 thermocouple data logger. DETAILED DESCRIPTION
[0063] As described above, the composition of the present invention comprises a part A composition comprising a (meth)acrylate component and an amine and a part B composition comprising a fatty acid peroxide.
[0064] When the Part A composition and the Part B composition are mixed together at room temperature (i.e., room temperature is about 25° C.), the mixed composition exhibits an open time of at least about 3 hours, but then reaches its peak cure temperature (or Tc) in less than about 1 hour. 峰 ), measured by a PICO Technologies USB TC-08 thermocouple data logger.
[0065] Part A
[0066] (Meth)acrylate component
[0067] Any suitable material containing at least one group having the formula:
[0068]
[0069] wherein R here is selected from H or C1 alkyl.
[0070] Advantageously, the group is a (meth)acrylate group or a (meth)acryloyloxy group, which is used to represent both acrylate and methacrylate groups, wherein R is H or methyl, respectively. The useful amount of the (meth)acrylate component is generally from about 20% to about 80% by weight of the total composition. Ideally, the composition of the present invention contains from about 50% to about 70% by weight of the (meth)acrylate component. In some embodiments, at least a portion of the (meth)acrylate component is isobornyl (meth)acrylate. For example, from about 5% to about 35% by weight of the composition of the present invention should be isobornyl (meth)acrylate.
[0071] The (meth)acrylate component may be present in the form of a polymer, a monomer, or a combination thereof. When present in the form of a polymer, the (meth)acrylate component may be a polymer chain to which at least one of a (meth)acrylate group or a (meth)acryloyloxy group is attached. The group may be located at a side chain or terminal position of the main chain, or a combination thereof.
[0072] Advantageously, at least two such groups may be present and may be located in terminal position. The (meth)acrylate component may have a polymer chain consisting of polyethylene, polyether, polyester, polyurethane, polyamide, epoxy resin, vinyl ester, phenolic resin, amino resin, oil-based substances, etc., or random or block combinations thereof, as is well known to those skilled in the art.
[0073] The polymer chain can be formed by polymerizing vinyl monomers. Illustrative examples of such vinyl monomers are: methyl (meth)acrylate, (meth)acrylic acid, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, phenyl (meth)acrylate, Cresyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, octadecyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, γ-(meth)acryloxypropyltrimethoxysilane, (meth)acrylic acid-ethylene oxide adduct, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate ethyl-2-perfluorobutyl ethyl ester, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, 2-perfluorohexadecylethyl (meth)acrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, dipentaerythritol monohydroxypentaacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate Ester, neopentyl glycol diacrylate, pentaerythritol tetraacrylate, 1,2-butylene glycol diacrylate, trimethylolpropane ethoxylate tri(meth)acrylate, glyceryl propoxylate tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, tri(propylene glycol) di(meth)acrylate, neopentyl glycol propoxylate di(meth)acrylate, 1,4-butylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate. These monomers may be used alone, or a plurality of them may be copolymerized.
[0074] Particularly desirable are (meth)acrylate monomers comprising monomers wherein the alcohol portion of the ester group contains C 1-8For example, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, cyclohexyl methacrylate, ethyl methacrylate, 1,3-butanediol dimethacrylate ("BDMA"), butyl methacrylate, and methyl methacrylate ("MMA").
[0075] The (meth)acrylate component may be from about 10 wt % to about 90 wt %, for example from about 60 wt % to 90 wt %, of the composition, based on the total weight of the composition.
[0076] amine
[0077] The composition of the present invention comprises at least one amine. The amine acts as a catalyst by accelerating or otherwise promoting the curing of the composition of the present invention. The amine is desirably a secondary or tertiary amine that is sterically hindered. Suitable amines include, for example, secondary or tertiary amines represented by the formula N-RR2R3, wherein R is selected from hydrogen (in the case of secondary amines) or alkyl (and its hydroxy substituted form), aryl, alkaryl or aralkyl, including C 1-10 Alkyl, C 6-18 Aryl, C 7-15 Alkyl and C 7-15 Aralkyl. The R2 group may be linked to the R3 group such that the nitrogen is embedded in a ring structure which itself may be fused to the aromatic ring system. In addition, R2 and R3 may each independently be R.
[0078] Particularly useful amines for inclusion in Part A of the compositions of the present invention include those of the structure A Amines,
[0079]
[0080] wherein R is optional, but when present, may occur 1-4 times and may be selected from C 1-5 Alkyl; halogen; -OH; -COOH; -CN; -NH2 or -NO2, the alkyl group may be interrupted by one or more heteroatoms and / or functionalized by halogen, -OH, -COOH, -CN, -NH2 or -NO2; X is C 1-5 Alkyl or C 7-20 Alkaryl, any of which may be interrupted by one or more heteroatoms, and the alkyl or alkaryl group is functionalized by at least one electron withdrawing group such as -CN or -NO2; and z is 1-3.
[0081] For example, you can choose the structure A An amine wherein X is a C1 alkyl or C7 alkylaryl substituted on the aromatic ring with at least one electron withdrawing group. Examples of such amines include:
[0082]
[0083] structure A The compounds in can be prepared from the following substances:
[0084]
[0085] The amine should be present in an amount of about 0.01 wt % to about 5 wt %. Ideally, the amine is present in an amount of about 0.05 wt % to about 2 wt %. More ideally, the amine should be present in an amount of about 0.3 wt % to about 0.7 wt %.
[0086] Vinyl terminated polybutadiene
[0087] When present, the vinyl terminated polybutadiene should be in liquid form at room temperature. The vinyl terminated polybutadiene should have a glass transition temperature below 0°C. The vinyl termination can be in the form of (meth)acrylate terminated, such as (meth)acrylate terminated polybutadiene-acrylonitrile copolymers such as HYCAR VTBN, or (meth)acrylate terminated polybutadiene such as HYCAR VTB, both from BF Goodrich. The vinyl terminated polybutadiene should be present in an amount of up to about 20 wt%, such as about 5 wt% to about 15 wt%.
[0088] Reactive acid component
[0089] The composition of the present invention may contain an acid or an acid ester as the reactive acid component, such as phosphoric acid or its derivatives, phosphoric acid esters, and sulfonic acid or their derivatives. The preferred reactive acid component is a phosphoric acid ester.
[0090] The acid may be selected from free radical polymerizable acids such as ethylenically unsaturated mono- or polycarboxylic acids, maleic acid, and crotonic acid. Desirable acids include methacrylic acid ("MAA") and acrylic acid.
[0091] The reactive acid component also regulates and decelerates the cure time of the composition.
[0092] Suitable phosphate esters include those represented by the formula:
[0093]
[0094] Here R 1 is H or CH3, and R 2 is H or a group represented by the following structure:
[0095]
[0096] Here R 1is H or CH3. Particularly useful phosphates are hydroxyl ethyl methacrylate phosphates sold under the trade names T-MULZ 1228 or HARCRYL 1228 or 1228M, each of which is available from Harcros Chemicals of Kansas City, Kansas. Also included are structures having at least one strong acid "active hydrogen" group or having at least one phosphonic acid active hydrogen group (R1R2POOH), such as hydroxyethyl diphosphonic acid, phosphonic acid and derivatives thereof; or oligomeric or polymeric structures having phosphonic acid functional groups or similar acid strength functional groups.
[0097] The reactive acid component, when present, is present at about 0.25% to about 15% by weight of the composition. Desirably, when the reactive acid component is a phosphate ester, it is present at about 1.0% to about 4.0% by weight of the composition.
[0098] 1,4-Quinone
[0099] Certain 1,4-quinones, when present, are useful for stabilizing the compositions of the present invention.
[0100] Naphthoquinone is one such 1,4-quinone; anthraquinone and benzoquinone are others.
[0101] Naphthoquinone may be used in an amount less than or equal to about 0.005 weight percent in the first part of the composition.
[0102] Desirably, the amount is less than or equal to about 0.004 wt %, such as less than or equal to about 0.0035 wt %.
[0103] Aryl phosphine
[0104] Aryl phosphines, when present, may be used in the first part A composition. Aryl phosphines may include tri(o-tolyl)phosphine, tri(4-methoxyphenyl)phosphine, diphenyl(p-tolyl)phosphine, diphenyl(o-tolyl)phosphine, tri(o-methoxyphenyl)phosphine, tri(p-tolyl)phosphine, diphenyl(2-methoxyphenyl)phosphine and tri(3,5-dimethylphenyl)phosphine, and of course triphenylphosphine.
[0105] Triphenylphosphine is used in an amount greater than or equal to about 0.5 wt %, such as greater than or equal to about 0.75 wt %.
[0106] Other additives
[0107] Part A compositions may also contain additional additives such as fillers, core-shell polymers, lubricants, thickeners and colorants. The fillers provide volume without sacrificing the strength of the adhesive and may be selected from high or low density fillers. In addition, certain fillers such as silica may impart rheology modification or small particle reinforcement. Commercially available examples include Cab-O-Sil 610 and AEROSIL R8200.
[0108] Of particular interest are low density fillers because the resulting final product has a substantially lower density than a product without the filler, but has substantially the same strength properties as if the filler were not present.
[0109] The core-shell polymer is ideally a graft copolymer of the "core-shell" type, or may also be a "shellless" cross-linked rubbery particle such as acrylonitrile-butadiene-styrene (ABS), methacrylate-butadiene-styrene (MBS) and methacrylate-acrylonitrile-butadiene-styrene (MABS). BLENDEX 338 is an ABS powder from GE Plastics.
[0110] Part B
[0111] Fatty acid peroxides
[0112] Instead of the now conventional benzoyl peroxide, a peroxide such as a fatty acid peroxide, such as lauroyl peroxide, is an ideal choice for the second part. In addition to lauroyl peroxide, the lauroyl peroxide has a straight chain C 2+ attached to the carbonyl carbon of the carboxylic acid that forms the peroxide. 11 Alkyl, other fatty acid peroxides may also be used. For example, fatty acid peroxides having a carbon atom chain length of 8 to 18 may be used. Of particular interest are those having 9, 11, 14, and 16 carbon atoms attached to the carbonyl carbon of the carboxylic acid that forms the peroxide.
[0113] Lauroyl peroxide is shown below:
[0114]
[0115] A commercially available example of lauroyl peroxide is sold by Arkema, Inc. under the trade name LUPEROX LP.
[0116] With C9, C 14 and C 16 The linear fatty acid peroxides are shown below as didecyl peroxide, dimyristyl peroxydicarbonate and dicetyl peroxydicarbonate, respectively, and are commercially available from Akzo Nobel NV as products of the product line under the PERKADOX trade name.
[0117] The fatty acid peroxide should be present in an amount of about 20% to about 60% by weight of the Part B composition. Ideally, the fatty acid peroxide is present in an amount of about 25% to about 50% by weight. More ideally, the fatty acid peroxide should be present in an amount of about 35% to about 45% by weight.
[0118] Epoxy resin
[0119] Epoxy resins are an optional component, but when present, may include cycloaliphatic epoxides, epoxy novolacs, bisphenol-A epoxies, bisphenol-F epoxies, bisphenol-A epichlorohydrin based epoxies, alkyl epoxides, limonene dioxide, and polyepoxides.
[0120] A desirable resin component is a cycloaliphatic epoxide sold by Dow Chemical under the trade name CYRACURE UVR-6110.
[0121] Another suitable resin component is a bisphenol-based liquid epoxy resin, such as those sold by Dow Chemical under the trade name "DER". Examples of "DER" products suitable for use in the present invention include DER 332 (diglycidyl ether of bisphenol-A); DER 330 (low viscosity, undiluted bisphenol-A liquid epoxy resin); DER 383 (low viscosity, undiluted bisphenol-A liquid epoxy resin); DER 354 (standard, bisphenol-F based liquid epoxy resin); DER 351 (low viscosity, liquid bisphenol-A / F resin mixture); DER 352 (low viscosity, liquid bisphenol-A / F resin mixture); DER 324 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin); DER 323 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin); DER 325 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin); and DER 353 (aliphatic glycidyl ether reactive diluent, modified liquid epoxy resin). A different brand of bisphenol-based liquid epoxy resin suitable for use herein is EPON 828 which is derived from bisphenol A and epichlorohydrin and is commercially available from Hexion Specialty Chemicals.
[0122] Another suitable resin component is an epoxy novolac resin, which is the product of epichlorohydrin and phenol-formaldehyde novolac and is sold by Dow Chemical under the trade name DEN. Examples of "DEN" products suitable for use in the present invention include DEN431 (a low viscosity semi-solid epoxy novolac resin); and DEN438 (a semi-solid epoxy novolac resin).
[0123] Other suitable epoxy resins include polyepoxides curable at ambient temperature or at a suitable elevated temperature with a catalyst or hardener. Examples of these polyepoxides include polyglycidyl ethers and poly(β-methylglycidyl) ethers obtainable by reacting a compound containing at least two free alcoholic and / or phenolic hydroxyl groups per molecule with an appropriate epichlorohydrin under alkaline conditions, or alternatively in the presence of an acidic catalyst and subsequent treatment with a base. These ethers can be prepared from acyclic alcohols such as ethylene glycol, diethylene glycol and higher poly(ethylene oxide) glycols, propane-1,2-diol and poly(propylene oxide) glycols, propane-1,3-diol, butane 1,4-diol, poly(oxytetramethylene) glycol, pentane-1,5-diol, hexane-2,4,6-triol, glycerol, 1,1,1-trimethylolpropane, pentaerythritol, sorbitol and poly(epichlorohydrin); cycloaliphatic alcohols such as resorcinol, p-cyclohexanediol, di(4-hydroxycyclohexyl)methane, 2,2-di(4-hydroxycyclohexyl)propane and 1,1-bis(hydroxymethyl)-cyclohex-3-ene; and alcohols with an aromatic core such as N,N-di(2-hydroxyethyl)aniline and p,p′-di(2-hydroxyethylamino)diphenylmethane. Or they may be prepared from mononuclear phenols such as resorcinol and hydroquinone; polynuclear phenols such as bis(4-hydroxyphenyl)methane, 4,4′-dihydroxybiphenyl, bis(4-hydroxyphenyl)sulfone, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (otherwise known as bisphenol A), 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane; and novolacs formed from aldehydes such as formaldehyde, acetaldehyde, trichloroacetaldehyde and furfural with phenols such as phenol itself and phenols substituted in the ring by chlorine atoms or by alkyl groups each containing up to 9 carbon atoms, such as 4-chlorophenol, 2-methylphenol and 4-tert-butylphenol.
[0124] Poly(N-glycidyl) compounds include, for example, those obtained by dehydrochlorination of the reaction product of epichlorohydrin with an amine containing at least two amino hydrogen atoms, such as aniline, n-butylamine, di(4-aminophenyl)methane and di(4-methylaminophenyl)methane; triglycidyl isocyanurate; and N,N′-diglycidyl derivatives of cyclic alkylene ureas such as ethylene urea and 1,3-propylene ureas, and hydantoins such as 5,5-dimethylhydantoin.
[0125] Epoxy resins having 1,2-epoxide groups attached to different kinds of heteroatoms may be employed, such as N,N,O-triglycidyl derivatives of 4-aminophenol, glycidyl-glycidyl esters of salicylic acid, N-glycidyl-N′-(2-glycidyloxypropyl)-5,5-dimethylhydantoin, and 2-glycidyloxy-1,3-bis(5,5-dimethyl-1-glycidylhydantoin-3-yl)propane.
[0126] Also suitable are epoxides derived from oils such as epoxidized soybean oil, epoxidized castor oil, etc. Also suitable are epoxides derived or derivable from unsaturated peracid oxidations, including epoxidized liquid rubbers.
[0127] Plasticizers
[0128] Plasticizers are often used in the Part B composition of a two-part composition. Plasticizers can also be used in the Part A composition. Plasticizers can be any liquid or soluble compound that contributes to the flexibility of the reactive module of the composition and / or can serve as a carrier vehicle for the other components of the composition. Examples include aromatic sulfonamides, aromatic phosphates, alkyl phosphates, dialkyl ether aromatic esters, polymeric plasticizers, dialkyl ether diesters, polyethylene glycol diesters, tricarboxylic acid esters, polyester resins, aromatic diesters, aromatic triesters (trimellitates), aliphatic diesters, epoxidized esters, chlorinated hydrocarbons, aromatic oils, alkyl ether monoesters, naphthenic oils, alkyl monoesters, paraffin oils, silicone oils, di-n-butyl phthalate, diisobutyl phthalate, di-n-hexyl phthalate, Di-n-heptyl phthalate, di-2-ethylhexyl phthalate, 7c9c-phthalates (linear and branched), diisooctyl phthalate, linear 6c, 8c, 10c phthalates, diisononyl phthalate, linear 8c-10c phthalates, linear 7c-11c phthalates, diisodecyl phthalate, linear 9c-11c phthalates, diundecane phthalate esters, diisodecyl glutarate, di-2-ethylhexyl adipate, di-2-ethylhexyl azelaic acid, di-2-ethylhexyl sebacate, di-n-butyl sebacate, diisodecyl adipate, triethylene glycol caprate-octanoate, triethylene glycol 2-ethylhexanoate, dibutoxyethyl adipate, dibutoxyethoxyethyl adipate, dibutoxyethoxyethyl formal, dibutoxyethoxyethyl sebacate, tri-2-ethylhexyl trimellitate esters, tris-(7c-9c (linear)) trimellitate, tris-(8c-10c (linear) trimellitate, triethyl phosphate, triisopropylphenyl phosphate, tributyl phosphate, 2-ethylhexyl diphenyl phosphate, trioctyl phosphate, isodecyl diphenyl phosphate, triphenyl phosphate, triaryl phosphate synthetics, tributoxyethyl phosphate, tris(-chloroethyl) phosphate, butylphenyl diphenyl phosphate, chlorinated organic phosphates, cresyl diphenyl phosphate, tris(dichloropropyl) phosphate, isopropylphenyl diphenyl phosphate, trixylenyl phosphate, tricresyl phosphate or diphenyl octyl phosphate.
[0129] Block copolymers
[0130] The block copolymer, when used, can be any block copolymer capable of contributing to the desired physical properties of the compositions of the present disclosure.
[0131] Block copolymer rubbers may be constructed using blocks of either butadiene or isoprene with styrene (eg, SBS, SIS, SEBS, and SB), commercial examples of which are available as KRATON D-1116 and other KRATON D-grade elastomers from Shell Chemical Co., and as VECTOR 2411 IP from Dexco.
[0132] It is possible to use a T below about 25°C g Other elastomers soluble in methacrylate / acrylate monomers can be substituted for the polychloroprene rubber and / or block copolymer rubber. Examples of this class are: homopolymers of epichlorohydrin and its copolymers with ethylene oxide, available as HYDRIN from Zeon Chemicals; acrylate rubber pellets, available as HYTEMP from Zeon; polyisoprene rubber; polybutadiene rubber; nitrile rubber; and SBR rubber (a random copolymer of butadiene and styrene).
[0133] Other block copolymers may be styrene maleic anhydride copolymers represented by the formula:
[0134]
[0135] wherein v is 1 to 12; w is 1 to 6; and n is 1 to 50.
[0136] Styrene maleic anhydride copolymers are well known and some are commercially available, for example, under the trade name SMAEF80 from Sartomer Company, Inc. of Exton, Pa. Styrene maleic anhydride copolymer refers to the copolymerization product of styrene and maleic anhydride characterized by alternating blocks of styrene moieties and maleic anhydride moieties.
[0137] Amphiphilic block copolymers may be particularly desirable. Arkema offers commercially available amphiphilic block copolymers under the trademark NANOSTRENGTH. Two forms of such block copolymers are currently available: SBM and MAM. SBM copolymers are reportedly made from polystyrene, 1,4-polybutadiene, and syndiotactic poly(methyl methacrylate).
[0138] In addition, a polymer material composed of polymethyl methacrylate ("PMMA") and polybutyl acrylate ("PB") can also be used. Such a polymer material is called polymethyl methacrylate-block-polybutyl acrylate-block polymethyl methacrylate copolymer ("MAM").
[0139] According to Arkema, MAM is a triblock copolymer consisting of about 70% PMMA and 30% PB. MAM is composed of different segments, which provide self-assembly capabilities at the molecular level. That is, M gives the polymer hardness, while A gives the polymer elastomeric properties.
[0140] The hard polymer segments tend to be soluble in (meth)acrylates, whereas the elastomeric segments provide toughness to the polymerized (meth)acrylates formed upon curing. MAMs also enhance mechanical properties without compromising inherent physical properties. MAMs are commercially available under the trade name NANOSTRENGTH, which currently exists in several different grades, namely E-21 and M-52N.
[0141] Arkema markets the NANOSTRENGTH product line as acrylic block copolymers that are miscible with a number of polymers, most of which, according to the manufacturer, are major industrial epoxy resins. See also U.S. Pat. No. 6,894,113, wherein in its abstract, the '113 patent mentions a thermoset having improved impact resistance. The impact resistance is derived from 1% to 80% of an impact modifier comprising at least one copolymer comprising SBM, BM, and MBM blocks, wherein each block is covalently linked to another, or has an intermediary that is covalently linked to one block and to another block by another covalent bond, M is a PMMA homopolymer or a copolymer comprising at least 50% by weight methyl methacrylate, B is incompatible with both the thermoset resin and the M block, and its glass transition temperature T is 0.0407 W / m. g is less than the operating temperature of the thermosetting material, and S is incompatible with the thermosetting resin, the B block and the M block, and its T g Or its melting temperature is greater than T of B g .
[0142] Another commercially available example of an amphiphilic block copolymer is a polyether block copolymer known under the trade name FORTEGRA 100 from Dow Chemical Co., which Dow describes as a low viscosity toughening agent designed for use as an efficient second phase in amine-cured epoxy systems. FORTEGRA 100 is reported to provide improved toughness without significantly affecting the viscosity, glass transition temperature, corrosion resistance, cure rate or chemical resistance of the final coating or composition. FORTEGRA 100 is also reported to be useful in formulating standard bisphenol A and bisphenol F epoxy systems because it does not participate in the epoxy curing reaction. As a second phase toughening agent, FORTEGRA 100 is promoted as being effective when formulated at a specific volume fraction of the finished film or part, typically 3% to 8% by dry volume is said to achieve a toughening effect.
[0143] Additional block copolymers include those containing both hydrophobic segments or portions and hydrophilic segments or portions having the general formula:
[0144] ―[(R 1 ) v ―(R 2 ) w ] n ―
[0145] Here R 1 are independently a hydrophobic olefin such as ethylene, propylene, 1-butene, 1-hexene, 3-methyl-1-pentene or 4-methyl-1-pentene, or a polymerizable hydrophobic aromatic hydrocarbon such as styrene; each R 2 is a hydrophilic anhydride such as maleic anhydride; v is 1 to 12; w is 1 to 6; and n is 1 to 50.
[0146] The ratio of the hydrophobic segments to the hydrophilic segments in the styrene maleic anhydride block copolymer can be at least 2:1, for example between 3:1 and 12:1. The hydrophilic segments in the block copolymer should contain anhydrides such as maleic anhydride. The hydrophobic segments in the block copolymer should contain at least one of ethylene, propylene, 1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene or styrene. Ideally, the block copolymer should be prepared with hydrophilic segments containing maleic anhydride and hydrophobic segments containing styrene.
[0147] Reference to the following patent documents shows amphiphilic block copolymers suitable for use herein and are hereby incorporated by reference. U.S. Patent No. 7,745,535 relates to and claims amphiphilic multi-block copolymers wherein at least one block is a profiled block consisting of: a) a hydrophilic mid-block made from one or more monomer units selected from the group consisting of acrylic acid, methacrylic acid and salts, esters, anhydrides and amides of acrylic acid and methacrylic acid, dicarboxylic acid anhydrides, carboxyethyl acrylate, and acrylamide; and b) hydrophobic end blocks; wherein the multi-block copolymer is insoluble in water, not dispersible in water, and not soluble or dispersible in C 1-3 In alcohol.
[0148] U.S. Patent No. 7,820,760 relates to and claims a curable adhesive epoxy resin composition comprising: (a) an epoxy resin; (b) an amphiphilic block copolymer comprising at least one epoxy resin miscible block segment and at least one epoxy resin immiscible block segment (wherein the immiscible block segment comprises at least one polyether structure, provided that the polyether structure of the immiscible block segment comprises at least one or more oxyalkylene monomer units having at least four carbon atoms); and (c) at least one curing agent. The amphiphilic block copolymer in the '760 patent is an all-polyether block copolymer, such as a PEO-PBO diblock copolymer or a PEO-PBO-PEO triblock copolymer. The amphiphilic block copolymer is present in an amount such that when the epoxy resin composition described in the '760 patent is cured, the resulting cured epoxy adhesive resin composition has an increased bond strength compared to an epoxy resin composition not containing the amphiphilic polyether block copolymer.
[0149] U.S. Pat. No. 7,670,649 relates to and claims a curable ambient cure high solids coating composition comprising: (a) an epoxy resin; (b) an amphiphilic block copolymer containing at least one epoxy resin miscible block segment and at least one epoxy resin immiscible block segment (wherein the immiscible block segment comprises at least one polyether structure, provided that the polyether structure of the immiscible block segment contains at least one or more oxyalkylene monomer units); and (c) a sufficient amount of a nitrogen-containing curing agent to cure the coating composition at an ambient temperature of less than about 60° C. Upon curing the epoxy resin composition, the toughness of the resulting cured epoxy resin composition increases.
[0150] U.S. Patent No. 6,887,574 relates to and claims a curable flame retardant epoxy resin composition comprising: (a) at least one flame retardant epoxy resin; (b) at least one amphiphilic block copolymer; and (c) a curing agent. The components are present in the curable composition in suitable amounts and ratios such that upon curing, the block copolymer self-assembles into a nanostructured morphology, such as a worm-like micelle morphology. The resulting cured product is reported to have a significantly increased high fracture resistance; and allows the use of flame retardant epoxy resins in applications where fracture resistance is a concern.
[0151] US Patent Application Publication No. 2008 / 0287595 relates to a composition comprising: (1) a thermosettable resin selected from epoxy resins, epoxy vinyl ester resins, unsaturated polyester resins, or mixtures thereof, and (2) an amphiphilic block copolymer dispersed in the thermosettable resin.
[0152] International Patent Publication No. WO 2010 / 008931 relates to a structural composite, which uses a block copolymer toughening agent to increase the fracture resistance (toughness) of the structural composite. The structural composite comprises (i) a carbon fiber reinforcement and (ii) a thermosetting resin composition; wherein the thermosetting resin composition comprises (a) a thermosetting resin and (b) at least one block copolymer toughening agent.
[0153] International Patent Publication No. WO 2009 / 018193 relates to a curable composition, a cured composition and a method of forming the same, which comprises an epoxy resin, a curing agent, an amphiphilic toughening agent and an inorganic nanofiller, wherein the toughening agent forms a second phase having at least one dimension on a nanometer scale.
[0154] The block copolymer may be used herein in an amount of up to about 50 wt %, desirably 5 wt % to 40 wt %, based on the total weight of the adhesive composition.
[0155] The glass transition temperature (T g ”) should be above about 40°C. In one embodiment, the T g Between about 40°C and about 155°C.
[0156] T of polymer g It is the temperature at which a polymer becomes brittle when cooled or softens when heated. More specifically, T g Definition of a pseudo-secondary phase transition in which a polymer, upon cooling, develops a glassy structure with properties similar to those of a crystalline material. Above T g When T g Sometimes described as the "softening temperature" of a polymer, but polymers will not soften below their Tg This is because, due to the nature of many non-crystalline polymers, the softening of the polymer may occur over a range of temperatures rather than suddenly occurring at a single temperature value. g The T of a polymer is usually the midpoint of the range, although the polymer may begin to soften at a different temperature. g It refers to the value measured according to ASTM E-1356.
[0157] When the polymer is heated above its T g Compared with the temperature below T g In addition to becoming brittle at temperatures above 40°C, the same polymer will generally become drier and less sticky. When pressure alone is applied, a sticky polymer will adhere to a surface more easily than a non-sticky polymer. As discussed below, adding a T above 40°C g And thus the importance of the copolymer being dry or only slightly tacky at this point will become more apparent.
[0158] Other additives
[0159] The Part B composition may contain further additives such as fillers, lubricants, thickeners and colorants. The fillers provide bulk without sacrificing the strength of the adhesive and may be selected from high or low density fillers.
[0160] Of particular interest are low density fillers because the resulting final product has a lower density than a product without the filler, but has substantially the same strength properties as if the filler were not present.
[0161] Packaging and mixing
[0162] The Part A composition and the Part B composition are each packaged in separate containers, such as bottles, cans, tubes or drums.
[0163] The Part A composition is mixed with the Part B composition in a volume ratio of about 3 to 50 to 1, such as about 5 to 20 to 1. Ideally, the volume ratio is 10:1.
[0164] The two parts can be mixed using a mixing nozzle having fluid input ports for the two components, suitable mixing operations, and the adhesive mixture is dispersed directly onto the surfaces to be bonded. An example of a commercially available mixing and dispersing device is sold under the trade name MIXPAC, available from Sulzer Mixpac USA of Salem, New Hampshire.
[0165] The two parts can also be mixed manually in a container such as a bowl, bucket or other container, but the operator needs to ensure that the mixing is complete. As an auxiliary means to ensure that the mixing is complete, the parts can be formulated with dyes or pigments so that after mixing, a third color is formed. For example, one part can have a yellow dye and the other part can have a blue dye so that after mixing, the completed adhesive composition will be green.
[0166] After mixing at room temperature, the composition exhibits an open time of at least about 3 hours, but then reaches its peak cure temperature (or Tc) in less than about 1 hour. 峰 ), as measured by a PICO Technologies USB TC-08 thermocouple data logger.
[0167] Also provided herein is a method for preparing a two-part adhesive composition. The method provides a first part comprising: (i) a (meth)acrylate component; and (ii) an amine; and provides a second part comprising: (i) a fatty acid peroxide.
[0168] In addition, a method for bonding a first surface to a second surface is provided herein. The method provides a two-part composition comprising: (a) a first part, the first part comprising: (i) a (meth)acrylate component; and (ii) an amine; and (b) a second part, the second part comprising: (i) a fatty acid peroxide, the first part and the second part are mixed, the mixed composition is applied to at least one of the first surface or the second surface, the first surface and the second surface are closely matched with the mixed composition, the mixed composition is between the two paired surfaces, and the composition is allowed to cure and bond the first surface to the second surface.
[0169] In these methods, the first and second parts are mixed in a volume ratio of 0.5 to 15 parts of the Part A composition to 1 part of the Part B composition.
[0170] Example
[0171] Example 1 - Part A Composition
[0172] In Table 1, Part A, a typical Part A composition was prepared from the listed ingredients in the amounts reported.
[0173] Table 1 Part A
[0174] Element Amount (g) Methyl Methacrylate 45.95 EDTA 0.1 Triphenylphosphine 0.5 Hydroquinone 0.05 BLENDEX 338 4.5 KRATON D 1155ES 22 HYPRO RLP 2000X 168VTB 13 wax 0.4 Methacrylic acid 10 Hydroxyethyl Methacrylate Phosphate 1 AEROSIL 200 1
[0175] In Table 2, Part A, three Part A compositions are shown: Sample No. 1 (control), which represents a composition from Table 1, Part A, wherein 2 wt % of p-diethanolamine toluene (p-DEA) is included in the Table 1, Part A composition; Sample No. 2, which represents a composition from Table 1, Part A, wherein 2 wt % of THQ-CN is added to 98 wt % of the Table 1, Part A composition; and Sample No. 3, which represents a composition from Table 1, Part A, wherein 2 wt % of THQ-NO2 is added to 98 wt % of the Table 1, Part A composition.
[0176] Table 2 Part A
[0177]
[0178] Example 2 - Part B Composition
[0179] In Table 1, Part B, a typical sample Part B composition was prepared from the listed ingredients in the amounts reported.
[0180] Table 1 Part B
[0181] Element Amount (g) PLURACOL V 10 10 BENZOFLEX 2088 20.4 Bisphenol A epichlorohydrin resin 21 ECONOPOLY 2N 1 11.5 VOSSEN BLAU 750LS 0.1
[0182] In Table 2, Part B, three compositions are shown: Sample No. 1, which represents a composition from Table 1, Part B, wherein 37% by weight of benzoyl peroxide is added to 63% by weight of the composition of Table 1, Part B; Sample No. 2, which represents a composition from Table 1, Part B, wherein 37% by weight of lauroyl peroxide is added to 63% by weight of the composition of Table 1, Part B; and Sample No. 3, which represents a composition from Table 1, Part B, wherein 37% by weight of lauroyl peroxide is again added to 63% by weight of the composition of Table 1, Part B.
[0183] Table 2 Part B
[0184]
[0185] Example 3 - Mixing
[0186] The Part A composition from Table 2 was mixed together with the Part B composition from Table 2 in a 10:1 volume ratio in a container, and a PICO Technologies USB TC-08 thermocouple data logger was placed in the mixed composition so that reactivity measurements of temperature and time could be recorded. Some of these measurements were collected in Table 3.
[0187] The composition was also applied to an anodized aluminum lap shear coupon and fit closely with another anodized aluminum lap shear coupon with an overlap of 0.5". The coupons were left to assess the fixture time. The fixture time measurements are also recorded in Table 3.
[0188] Table 3
[0189]
[0190] Other measurement results are Figure 1 In Figure 1 The data are accumulated every minute to show the onset of cure (or T 发动 ) time required, peak exothermic temperature (or T 峰 ) and the duration of the entire curing curve.
[0191] It can be seen that for the control sample (sample No. 1), T 发动 The mixture starts within about 1 to about 2 minutes after mixing and forms a T in about 7 to about 8 minutes. 峰 In contrast, sample No. 2 required nearly 4 hours (between about 202 and 230 minutes) to 发动 The T 峰 Sample No. 3 required more than 3 hours (between about 181 and 198 minutes) for T 发动 It starts and forms T in about 199 to about 201 minutes. 峰 .
Claims
1. A two-part curable composition comprising: (a) a first part, the first part comprising: (i) (meth)acrylate component; (ii) amines; and (b) a second part, the second part comprising: (i) fatty acid peroxides, in, The fatty acid peroxide is present in an amount of 20 wt % to 60 wt % based on the second part composition, Wherein the amine is selected from: wherein R is optional, but when present, occurs 1-4 times and can be selected from C 1-5 Alkyl; halogen; -OH; -COOH; -CN; -NH2 or -NO2, the alkyl group may be interrupted by one or more heteroatoms and / or functionalized by halogen, -OH, -COOH, -CN, -NH2 or -NO2; X is C 1-5 Alkyl or C 7-20 an alkaryl group, any of which may be interrupted by one or more heteroatoms, and the alkyl or alkaryl group is functionalized by at least one electron withdrawing group; and z is 1-3.
2. The composition according to claim 1, wherein When the first part composition and the second part composition are mixed together, the composition exhibits an open time of at least 3 hours, but then cures in less than 60 minutes as measured by a PICO Technologies USB TC-08 thermocouple data logger.
3. The composition according to claim 1, wherein The first part composition additionally comprises at least one of a vinyl terminated polybutadiene in liquid form at room temperature; a reactive acid component; a 1,4-quinone and a triarylphenylphosphine or an alkarylphenylphosphine.
4. The composition according to claim 3, wherein The 1,4-quinone is naphthoquinone or benzoquinone.
5. The composition according to claim 3, wherein The 1,4-quinone is present in an amount less than or equal to 0.05 wt%.
6. The composition according to claim 3, wherein The triarylphenylphosphine or alkarylphenylphosphine is present in an amount greater than or equal to 0.5 wt%.
7. The composition according to claim 1, wherein The (meth)acrylate component of the first composition is selected from methyl (meth)acrylate, (meth)acrylic acid, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, tert-butyl ... esters, dodecyl (meth)acrylate, phenyl (meth)acrylate, tolyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, octadecyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, γ-(meth)acryloyloxypropyltrimethoxysilane, (meth)acrylic acid-ethylene oxide adduct, trifluoromethyl (meth)acrylate Ester, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethylmethyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethylmethyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, 2-perfluorohexadecylethyl (meth)acrylate, pentaerythritol triacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, pentaerythritol tetraacrylate, trimethylolpropane ethoxylate tri(meth)acrylate, glyceryl propoxylate tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, tri(propylene glycol) di(meth)acrylate, neopentyl glycol propoxylate di(meth)acrylate, polyethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and combinations thereof.
8. The composition according to claim 1, wherein The (meth)acrylate component of the first composition is selected from ethoxylated trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, dipentaerythritol monohydroxypentaacrylate, 1,2-butanediol diacrylate, 1,4-butanediol di(meth)acrylate, and combinations thereof.
9. The composition according to claim 1, wherein The electron withdrawing group is -CN or -NO2.
10. The composition according to claim 1, wherein The amine is selected from:
11. The composition according to claim 3, wherein The reactive acid component is sulfonic acid or a sulfonic acid derivative.
12. The composition according to claim 3, wherein The reactive acid component is selected from phosphoric acid, phosphoric acid derivatives and phosphoric acid esters.
13. The composition according to claim 3, wherein The reactive acid component is hydroxyethyl methacrylate phosphate.
14. The composition according to claim 1, wherein The fatty acid peroxide has 8 to 18 carbon atoms.
15. The composition according to claim 1, wherein The fatty acid peroxide is selected from the group consisting of lauroyl peroxide, didecyl peroxide, dimyristyl peroxydicarbonate and dicetyl peroxydicarbonate.
16. The composition of claim 1 further comprising an epoxy resin in the second part composition.
17. The composition according to claim 16, wherein The epoxy resin of the second composition is selected from the group consisting of multifunctional epoxides and combinations thereof.
18. The composition according to claim 16, wherein The epoxy resin of the second composition is selected from the group consisting of cycloaliphatic epoxides, epoxy novolac resins, bisphenol-F epoxy resins, bisphenol-A epichlorohydrin-based epoxy resins, alkyl epoxides, and combinations thereof.
19. The composition of claim 18, wherein the bisphenol-A epichlorohydrin based epoxy resin is a bisphenol-A epoxy resin.
20. The composition of any one of claims 1, 18 and 19, wherein the composition further comprises limonene dioxide in the second part composition.
21. The composition according to claim 16, wherein The epoxy resin of the second part composition is a liquid bisphenol A epichlorohydrin epoxy resin.
22. A method for preparing a two-part adhesive composition, the method comprising: (a) providing a first part, the first part comprising: (i) (meth)acrylate component; and (ii) amines; and (b) providing a second part, the second part comprising: (i) fatty acid peroxides, Wherein, based on the second part of the composition, the fatty acid peroxide is present in an amount of 20 wt % to 60 wt %, Wherein the amine is selected from: wherein R is optional, but when present, occurs 1-4 times and can be selected from C 1-5 Alkyl; halogen; -OH; -COOH; -CN; -NH2 or -NO2, the alkyl group may be interrupted by one or more heteroatoms and / or functionalized by halogen, -OH, -COOH, -CN, -NH2 or -NO2; X is C 1-5 Alkyl or C 7-20 an alkaryl group, any of which may be interrupted by one or more heteroatoms, and the alkyl or alkaryl group is functionalized by at least one electron withdrawing group; and z is 1-3.
23. The method according to claim 22, wherein: The first part composition and the second part composition are mixed in a volume ratio of 0.5 to 15 parts of the first part composition to 1 part of the second part composition.
24. A method of bonding a first surface to a second surface, the method comprising: A two-part composition is provided, comprising: (a) a first part, the first part comprising: (i) a (meth)acrylate component; and (ii) amines; and (b) a second part, the second part comprising: (i) fatty acid peroxides, mixing the first part with the second part, applying the mixed composition to at least one of the first surface or the second surface, The first surface and the second surface are closely matched with the mixed composition, and the mixed composition is between the two paired surfaces, and allowing the composition to cure and bond the first surface to the second surface, Wherein, based on the second part of the composition, the fatty acid peroxide is present in an amount of 20 wt % to 60 wt %, Wherein the amine is selected from: wherein R is optional, but when present, occurs 1-4 times and can be selected from C 1-5 Alkyl; halogen; -OH; -COOH; -CN; -NH2 or -NO2, the alkyl group may be interrupted by one or more heteroatoms and / or functionalized by halogen, -OH, -COOH, -CN, -NH2 or -NO2; X is C 1-5 Alkyl or C 7-20 an alkaryl group, any of which may be interrupted by one or more heteroatoms, and the alkyl or alkaryl group is functionalized by at least one electron withdrawing group; and z is 1-3.
